CONSUMPTION BEHAVIOR MODEL OF SANTRI AT MODERN PUTRI BOARDING SCHOOL, MALANG REGENCY, EAST JAVA - Riski, Dita Suci Novia; Nasikh, Nasikh; Wulandari, Dwi (Research and Development Journal of Education, 2025)
This study examines the consumption behavior model of santri (Islamic boarding school students) at a Modern Putri Boarding School in Malang Regency, East Java, as well as analyzing its impacts and the pesantren's policies regarding it. This qualitative research, employing an iterative thematic inquiry method, was conducted using in-depth interviews, observation, and documentation studies. The findings indicate that santri consumption behavior is complex, influenced by the interaction between personal needs, accessibility, preferences shaped by trends and peer influence, and the ability to manage pocket money. The impacts of this behavior encompass financial, social, and psychological aspects. Financially, santri show variations in pocket money management, with some successfully saving while others experience difficulties. There are differences in daily expenditures within the boarding school and during student visits, indicating a "release" of consumption when access is broader. Socially, peer influence can be both positive (financial discipline) and negative (encouraging consumerism), while psychologically, santri experience self-control but also the potential for impulsive urges due to trends. The pesantren's policies in regulating santri consumption tend to be informal, through the guidance of ustadzah (female teachers) and regulation of access to resources. However, there is no structured formal financial literacy education. This study concludes the importance of developing comprehensive financial literacy programs in pesantren to equip santri with wise money management skills in accordance with Islamic values.